The Approach of the Business Sector to Responsible Research and Innovation (RRI) - Annamaria Inzelt; Laslo Csonka (Foresight and STI Governance, 2017)
This paper focuses on attitudes towards responsible research and innovation (RRI) and the approaches of business organizations, in that this emerging concept anticipates and assesses the various effects of research and innovation practice. The importance of this issue is highlighted by recent scandals in the automotive industry (and elsewhere). Much of our attention is devoted to corporate responsibility in the fields of research and innovation — an important value that goes beyond research. Our investigation was based on 27 case studies relating to companies from 14 European countries. The selection criteria went beyond those used most frequently in RRI studies, covering fields wider than emerging techno-sciences.